Birth Defects Among Fetuses and Infants of US Women With Evidence of Possible Zika Virus Infection During Pregnancy. Issue 3 (September 2017) - Honein, M.A.; Dawson, A.L.; Petersen, E.E.; Jones, A.M.; Lee, E.H.; Yazdy, M.M.; Ahmad, N.; Macdonald, J.; Evert, N.; Bingham, A.; Ellington, S.R.; Shapiro-Mendoza, C.K.; et al.
Abstract : (JAMA. 2017;317(1):59–68) Fetal microcephaly and other brain abnormalities have been associated with Zika virus infection during pregnancy. However, the magnitude of risk for fetuses of infected parturients remains unknown. It is also unclear whether women with symptomatic Zika virus disease are more likely to have adverse pregnancy outcomes than those with asymptomatic infection. This report analyzed data obtained from the US Zika Pregnancy Registry (USZPR) to determine the proportion of fetuses or infants with birth defects likely to be associated with maternal Zika virus infection among women in the United States. The investigators also evaluated whether the proportion of infants with birth defects differed based on the presence of maternal symptoms of Zika virus infection or by trimester of possible infection.